Angola’s persistent drought - Blanes, Ruy Llera; Cardoso, Carolina Valente; Bahu, Helder Alicerces; Fortuna, Cláudio (Africa is a Country, 2020)
In southern Angola, a preventable humanitarian crisis deepens. The government bears much of the responsibility.